Effective long-term treatment with moss-produced factor H by overcoming the antibody response in a mouse model of C3G - Todor Tschongov; Swagata Konwar; Swagata Konwar; Jessika Kleindienst; Paulina Dabrowska-Schlepp; Andreas Busch; Andreas Schaaf; Christoph Schell; Manuel Rogg; Karsten Häffner (Frontiers in Immunology)
Complement-associated disorders are caused by the dysregulation and disbalance of the complement system, especially excessive activation. Most drugs that target the complement system are designed to inhibit the complement pathway at either the proximal or terminal levels. The use of a natural complement regulator such as factor H (FH) could provide a superior treatment option by restoring balance to an overactive complement system. We recently reported the moss-based production of an analog of human FH with an optimized glycan profile (CPV-104), which showed in vitro and in vivo characteristics comparable to its human counterpart. Here, we follow up our previous work, focusing in more detail on the time course and long-term efficacy of CPV-104 treatment in FH-deficient (FH–/–) mice. The analysis of long-term treatment effects following multiple injections of human FH into mice was previously hindered by the immune response, so we developed a protocol for the sustained depletion of CD20+ B-cells and CD4+ T-cells, preventing antibody formation without influencing the C3G phenotype. Using this dual-depletion method, we were able to complete dosing interval experiments in FH–/– mice, administering up to three injections of CPV-104 at different intervals. Repeated CPV-104 administration was able to lastingly resolve C3 deposits, offering additional rationale for the clinical testing of CPV-104 in human C3G patients. Moreover, our novel dual-depletion method has the potential for adaptation to different mouse models, allowing the testing of multiple doses of other therapeutic proteins.